(untitled) (Vietnam Journal of Community Medicine, 2026)
HOSPITAL Objective: To describe selected clinical and paraclinical characteristics and to evaluate treatment outcomes in patients with stage II–III rectal cancer who received preoperative concurrent chemoradiotherapy at Thanh Hoa Provincial Oncology Hospital. Materials and Methods: A retrospective descriptive study with longitudinal follow-up was conducted on 75 patients with low and middle-rectal cancer, stage II–III, who underwent preoperative concurrent chemoradiotherapy at Thanh Hoa Provincial Oncology Hospital between January 2018 and December 2022. Results: The most common age group was 40–59 years (54.7%). The youngest patient was 34 years, the oldest 83 years, with a mean age of 56.7 ± 12.3 years. The male-to-female ratio was approximately 2.7:1. The majority of patients presented for medical evaluation within ≤ 3 months after the onset of initial symptoms (89.3%). Common clinical symptoms included mucous and bloody stools (86.7%), tenesmus (64.0%), and difficulty in defecation (46.7%). Low rectal cancer accounted for 56.0% of cases. On endoscopy, the predominant tumor morphology was exophytic (polypoid) lesions (86.7%), while ulcerative–exophytic lesions accounted for 13.3%; no purely ulcerative or infiltrative forms were observed. The proportions of stage II and stage III disease were 41.3% and 58.7%, respectively. All patients (100%) underwent radical surgery, of whom 65.3% received sphincter-preserving procedures. After treatment, 20.0% progressed to stage III and 5.3% to stage IV. Treatment response showed a statistically significant improvement (p < 0.05). The complete response rate was 8.0%, while the overall response rate after concurrent chemoradiotherapy was 86.7%. Local progression was observed in 2.7% of cases (regional lymph node enlargement). The median follow-up duration was 42.6 months. The disease-free survival (DFS) rates at 1, 3, and 5 years were 100.0%, 78.7%, and 60.3%, respectively.